2018
DOI: 10.1017/jmo.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership, trust in leader and creativity: The mediated mechanism and an interacting effect

Abstract: This study examines the relationship between ethical leadership and employee creativity with mediating role of trust in leader and moderating role of openness to experience. Data were collected from 205 supervisor–subordinate small textile firms across Pakistan. Confirmatory factor analysis confirmed the distinctiveness of variables used in our study. The results confirmed that ethical leadership promotes creativity at workplace, while trust in leader mediates the effect of ethical leadership on creativity. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 129 publications
(153 reference statements)
5
92
0
5
Order By: Relevance
“…First, we found a good number of studies which found positive relationship between Big Five traits and innovative behaviors (Prabhu, Sutton, & Sauser, ; Raja & Johns, ; Sung & Choi, ). And based on these arguments earlier studies controlled for other types of personality traits while examining the effect of one type on outcome variable (Javed, Rawwas, Khandai, Shahid, & Tayyeb, ; Michael, Hou, & Fan, ; Xu, Jiang, & Walsh, ). Moreover, to find out whether we can generalize our results across different cultures based on responses collected from Canada and Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…First, we found a good number of studies which found positive relationship between Big Five traits and innovative behaviors (Prabhu, Sutton, & Sauser, ; Raja & Johns, ; Sung & Choi, ). And based on these arguments earlier studies controlled for other types of personality traits while examining the effect of one type on outcome variable (Javed, Rawwas, Khandai, Shahid, & Tayyeb, ; Michael, Hou, & Fan, ; Xu, Jiang, & Walsh, ). Moreover, to find out whether we can generalize our results across different cultures based on responses collected from Canada and Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…Thirdly, an implicit ethical structure such as ethical leadership and ethical culture can promote innovation on the part of the employees. Entrepreneurs with high ethical standards create an ethical climate that caters to the interests and wellbeing of others, thus increasing employees' spirit of adventure and sense of psychological security, and promoting employee innovation [65][66].…”
Section: Entrepreneurial Ethics and Sustainable Growth Of New Venturementioning
confidence: 99%
“…Continual scandals in business and public sectors over the last decades have increased interest in ethical leadership (Khokhar & Zia-ur-Rehman, 2017;Marquardt, Brown, & Casper, 2018). The increase in the importance of ethics in business and management has led many scholars to focus on ethical leadership behavior (Ardelean, 2015;Eubanks, Brown, & Ybema, 2012;Javed, Rawwas, Khandai, Shahid, & Tayyeb, 2018;Mayer, Kuenzi, Greenbaum, Bardes, & Salvador, 2009;Northouse, 2013;Resick et al, 2011;Trevino, den Nieuwenboer, & Kish-Gephart, 2014). Moreover, it has provided opportunities for researchers to investigate methods that produce increased knowledge of ethical behavior in organizations that can result in facilitating and sustaining the development of ethical leadership behavior.…”
Section: Introductionmentioning
confidence: 99%